A parametric study of the mechanical and dispersion properties of cubic lattice structures. (August 2016) - Junyi, L.; Balint, D.S.
Abstract: A study of the mechanical and dispersion properties of cubic lattice structures have been conducted to assess the viability of designing a multifunctional and lightweight lattice structure with excellent static properties and elastic band gaps for vibration attenuation. In this study, the parameters that characterises the mechanical properties for stiffness and strength to be used as sandwich structure core materials were identified. A parametric study on the geometry of the lattice structures on the static properties was performed in order to determine the optimal geometry for these applications. The trends relating the geometric parameters to the mechanical properties of the lattice topologies were found and discussed. Local resonators were then added to the optimal geometries to create the band gaps that will attenuate vibrations at given frequency ranges. The tuned frequency was set to be 500 Hz in this study. The effects of the geometric parameters on the band gap widths produced by the introduction of the resonators were studied and the trends were found to be similar for all topologies. The results of this study indicate that the addition of local resonators to introduce band gaps is only viable when the stiffness and strength of the lattice without the resonators are sufficiently large, so that the increase in density will not be too significant. Lastly, band gaps around the tuned frequencies were observed for one of the topologies without the resonators. Since these band gaps do not result in an increase in mass, tuning the geometry to move the band gaps to the desired frequency ranges is a preferred strategy over the addition of local resonators.